2006
DOI: 10.1007/s11414-006-9024-4
|View full text |Cite
|
Sign up to set email alerts
|

Child Sociodemographic Characteristics and Common Psychiatric Diagnoses in Medicaid Encounter Data: Are they Valid?

Abstract: This study describes the rate that Medicaid encounter data on gender, race/ethnicity, and diagnosis matched information in the medical record, among a statewide sample of Medicaid children who received ongoing care for attention deficit hyperactivity disorder (ADHD), conduct disorder (CD), and major depression (MD) in outpatient specialty mental health clinics in 1998-1999. The match rate for gender was 99%; and for race/ethnicity it was 71.8%, 90.5%, and 89.7% for Caucasian, African American, and Hispanic chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Similar to a previous report, 59 this approach increased the specificity of case ascertainment. Moreover, KPSC has stringent criteria that must be met for the diagnosis of ADHD: (1) every child has a standardized form, "The Child Behavior Checklist," that parents and teachers fill out to describe the child' s behavioral and emotional problems and (2) 61,62 Although one may argue that the diagnosis of ADHD by health care professionals with appropriate expertise to diagnose and treat the condition is a reflection of validity, here we would also like to underline that we have not compared whether the diagnostic validity has increased by the KPSC approach or whether it is any better than a diagnosis made by parent and teacher reports with rapid pediatrician assessment.…”
Section: Discussionsupporting
confidence: 69%
“…Similar to a previous report, 59 this approach increased the specificity of case ascertainment. Moreover, KPSC has stringent criteria that must be met for the diagnosis of ADHD: (1) every child has a standardized form, "The Child Behavior Checklist," that parents and teachers fill out to describe the child' s behavioral and emotional problems and (2) 61,62 Although one may argue that the diagnosis of ADHD by health care professionals with appropriate expertise to diagnose and treat the condition is a reflection of validity, here we would also like to underline that we have not compared whether the diagnostic validity has increased by the KPSC approach or whether it is any better than a diagnosis made by parent and teacher reports with rapid pediatrician assessment.…”
Section: Discussionsupporting
confidence: 69%
“…Inpatient claims were included if they occurred after the date of the long-term-care claim, and outpatient claims were included if they occurred in the same month as the long-term-care claim. Studies that examined the reliability of Medicaid claims data for use in research on psychiatric disorders have found the primary and secondary diagnosis variables to be reliable (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…We lacked structured interview data for psychiatric diagnoses, for example. However, diagnostic concordance for psychiatric diagnoses between medical records and Medicaid claims is often high (Walkup et al, 2000), including recent reports of agreement between 89% to 98% for common psychiatric conditions in childhood (Knapp et al, 2006). Support for pharmacy refill persistence as an ART adherence measure is generally strong, with correlations found with various biological measures (e.g., Grossberg et al, 2004), including a study of younger patients (Watson and Farley, 1999).…”
Section: Discussionmentioning
confidence: 99%